Social Capital and Community Participation in the Development of the Aquaculture Center in Soko Village-Indonesia - Aprilia, Erlindah; Prayitno, Gunawan; Usman, Fadly; Biloshkurska, Nataliia V.; Siankwilimba, Enock; Simamba, Habeenzu (Perencanaan Wilayah dan Kota FT UB, 2023)
Aquaculture fisheries are important in developing the national fisheries sector to improve and sustain the community’s welfare. Social capital becomes community support in dealing with various problems in fishery areas. This research aims to identify the relationship between social capital and community participation in implementing the development of Soko Village as an aquaculture center in Glagah District, Lamongan Regency. The population in this study were the heads of families (households) of cultivators, with a sample of 181 families. The analysis used is the structural equation model (SEM). The result shows that the social capital of the Soko Village community consists of trust, networks, and norms. The relationship between social capital and community participation in implementing the aquaculture center development program indicates a significant positive relationship between social capital and community participation.